NILAI SOSIAL DALAM NOVEL LONDON LOVE STORY KARYA TISA TS - Giawa, Ayodi (Universitas Nias Raya, 2023)
The study is background to the social value in Tisa TS' London love story that conveys a social taste in literature that is not directly and needs to be used as an alternative to the study of prose studies in Indonesian language and literary students and other students. The study is intended to describe the social value of London love story by TS. the research approach and method used in the study are qualitative and descriptive. The source of blood in this study is TTS 'London love story. The data analysis techniques in this study are data reduction, data presentation and inference/verification. The findings suggest that the London love story by Tisa TS' novel contained twelve social values in between; (1) the value of compassion consists of five social virtues of devotion, helpfulness, family, loyalty and concern (2) the value of responsibility and concern (2) there are three parts of both self-sufficiency, discipline, and empathy (3) the value of harmony in life lies the four social virtues of justice, tolerance, cooperation, and democracy. The researchers' advice should make the study a basis for comparison to the rest of the researchers and be expected to supplement new insights into bahsa science and Indonesian literature in particular asa mandate